2018
DOI: 10.1002/ieam.4092
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term to long‐term extrapolation of lethal effects of an herbicide on the marine mysid shrimpAmericamysis Bahiaby use of the General Unified Threshold Model of Survival (GUTS)

Abstract: Risk assessments for plant protection products and their active ingredients that are based on standard laboratory tests performed under constant exposure conditions may result in an overestimation of risks because exposure in the environment is often characterized by a few short peaks. Here, the General Unified Threshold Model of Survival (GUTS) was used to conduct a refined risk assessment for the herbicide tembotrione and its effects on the marine invertebrate Americamysis bahia, for which the standard chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It can also be that the observed survival‐concentration time data are best predicted using a combination of the GUTS‐RED‐SD and GUTS‐RED‐IT model, that is, the “proper” GUTS‐RED model (Jager and Ashauer 2018). However, this model is rarely used in published GUTS modeling studies (Focks et al 2018; Gabsi et al 2019; Dalhoff et al 2020), because researchers are typically able to explain the observed survival‐concentration time pattern with one of the 2 simpler models (IT or SD). The “proper” GUTS‐RED model is also more difficult to calibrate, because it consists of 5 instead of 4 parameters and the software used (openGUTS) does not yet support calibration of the proper GUTS‐RED model (Jager 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…It can also be that the observed survival‐concentration time data are best predicted using a combination of the GUTS‐RED‐SD and GUTS‐RED‐IT model, that is, the “proper” GUTS‐RED model (Jager and Ashauer 2018). However, this model is rarely used in published GUTS modeling studies (Focks et al 2018; Gabsi et al 2019; Dalhoff et al 2020), because researchers are typically able to explain the observed survival‐concentration time pattern with one of the 2 simpler models (IT or SD). The “proper” GUTS‐RED model is also more difficult to calibrate, because it consists of 5 instead of 4 parameters and the software used (openGUTS) does not yet support calibration of the proper GUTS‐RED model (Jager 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of data for neonicotinoid insecticides and several aquatic arthropod species (comprising crustaceans and insects), Focks et al (2018) also concluded that the application of GUTS modeling for refinements in ERA appeared possible for most of the presented species–compound combinations, when the results of both the GUTS‐RED‐SD and GUTS‐RED‐IT models were used. Gabsi et al (2018) advocated that the selection of the model type (SD or IT) to be used in the risk assessment should be based on those toxicodynamic parameters that best reflect the toxic mode of action of the compound under evaluation. For example, they showed that the GUTS‐RED‐IT model parameters more successfully captured the slow‐acting mechanism of the herbicide tembotrione when predicting the response of time‐variable exposures on the mysid shrimp Americamysis bahia than the GUTS‐RED‐SD.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly used for research purposes, initially at constant exposure concen trations (Jager and Kooijman, 2005;Hesketh et al, 2016;Kretschmann et al, 2012), GUTS is today more and more employed to account for time-variable exposure (Ducrot et al, 2010;Focks et al, 2018;Nyman et al, 2012;Gabsi et al, 2018). GUTS models are also used for ERA, for example at Tier-2C assessment in combination with Tier-2B assessment based on SSD approaches (see Brock et al 2021, and Figure 6 in EFSA PPR Panel 2018a).…”
Section: Extrapolation Of Effects Of a Tested Exposure Pattern To Oth...mentioning
confidence: 99%